Determination of mass and center of mass coordinates of the aircraft in the performance of its modernization - Пучков, Ю.П.; Зімін, В.Є.; Юрченко, О.І. (Proceedings of National Aviation University (archive), 2009)
The questions related to renewal option of aircraft exploitation without his certification after the lead through on him of modernization with the purpose of satisfaction to the ICAO requirements are examined in the offered article.